Indonesian-English Code-Switching in Gogirl! Magazine: Types and Features - Priyatno Ardi; Agatha Elma Febiyaska (Yayasan Visi Intan Permata, 2019)
The present study investigates the types and features of Indonesian-English code switching in GoGirl! Magazine of March to May 2016 editions. Content analysis was employed in this study. The results of the analysis revealed that 1.355 cases of Indonesian-English code switching appeared in the magazines. The types of code-switching included alternation, insertion, and congruent lexicalization. The features of code switching in the magazines were several constituents, non-nested a b a, length and complexity, discourse particles and adverbs, peripherality, single constituent, nested a b a, content words, linear and structural equivalence, multi-constituent code-mixing, non-constituent mixing, and triggering. The researchers concluded that the mostly used type was alternation and non-nested a b a is the mostly used feature in GoGirl! Magazine.